Bacterial Cellulose as a Raw Material for Food and Food Packaging Applications - Azeredo, Henriette M. C.; Barud, Hernane; Farinas, Cristiane S.; Vasconcellos, Vanessa M.; Claro, Amanda M. (Frontiers in Sustainable Food Systems, 2019)
Bacterial cellulose (BC) has been produced for a number of applications, mainly focused on the biomedical area. Although there is a variety of interesting applications of BC for food and food packaging, only a few have been explored to the moment, since the high cost of BC production is usually considered as a limiting factor. On the other hand, several cost-effective culture media have been proposed, contributing to reduce BC production costs. This article overviews the bioprocess conditions that affects BC production and the main possible applications of BC for food and food packaging purposes.